FORMAÇÃO DE PROFESSORES E O TRABALHO COM AS JUVENTUDES NA EDUCAÇÃO PROFISSIONAL - da Silva Barros, Lucian (2022)
This text, which is part of the results of a master's dissertation in education, aims to present and discuss the experience of Senac SP in the construction and conduction of the Senac Learning Program (PSA), focused on training teachers to work in this course. Such program, complies with the provisions of Law No. 10,097 of December 19, 2000, which regulates the hiring of young apprentices in Brazil. Based on the observation of the daily life of one of its educational units, the focus of discussion lies on the training of teachers and the attention given to the young people served. Initially, there is a discussion about professional education in Brazil, understood as a teaching modality historically focused on the training of workers. The training of teachers to work in this field is discussed from a perspective of overcoming the technical and instrumental view. It is recognized that teaching action should be built on the basis of flexibility, sensitivity and respect for students' knowledge, with a view to building a fundamental didactic that guides all pedagogical work. Senac São Paulo's experience, supported by its pedagogical proposal, in working with young apprentices, demonstrates new possibilities of educational practice and the necessary constant review of teaching practices, of the curricula of the forms of assessment. In order to elucidate such issues, reports of educational daily life are presented throughout the text, which praise the dynamism and plurality that the teaching work with young people, so that they can act in the society in which they live as agents of change and transformation.